Sonic hedgehog signaling: Alternative splicing and pathogenic role in medulloblastoma - Meiyu Qu; Qiangqiang He; Jiahao Luo; Tingyu Shen; Ruibo Gao; Yana Xu; Chengyun Xu; Muhammad Qasim Barkat; Ling-Hui Zeng; Ximei Wu (Genes and Diseases, 2023)
Alternative splicing (AS) produces the different mRNA splicing bodies, which are then translated into multiple protein isoforms and participate in various biological functions. With a deeper understanding of alternative splicing through the study of transcriptomes using high-throughput sequencing-based methods, the correlation between aberrant AS and diseases triggered a great concern, especially abnormal AS and cancer. Medulloblastoma (MB) is an intracranial tumor in children. Sonic hedgehog MB (SHH-MB) accounted for approximately 30% of MB, which is associated with the activation of SHH signaling. Growing evidence shows that aberrant AS is closely related to the tumorigenesis of MB. Here, we briefly introduced the AS and its mechanism. Next, we described canonical/noncanonical hedgehog signaling and its correlation with MB. The main description focused on AS of various regulators in canonical hedgehog signaling in MB. In addition, we also described AS of various regulators in noncanonical hedgehog signaling. Meanwhile, activated hedgehog signaling also induces AS in MB. Then, we pointed out that aberrant AS of hedgehog signaling is associated with different MB subgroups. Finally, we summarized the therapeutic applications of targeted AS in cancer treatment. In summary, further understanding of AS in SHH-MB could develop therapeutic targets for splicing factors which may be a novel therapeutic strategy.